Clinical and anamnestic features of acetonemic syndrome in children with patholigy of the digestive system - Khilchevska, V. S. (Journal of Education, Health and Sport, 2018)
In the practice of a gastroenterologist, diseases that are accompanied by a clinic of acetone syndrome are of particular relevance. The study involved 38 children with acetonemic syndrome on the background of gastroenterological pathology. Two clinical groups of observations were formed: І group included 25 children with moderate ketosis, ІІ group - 13 children with severe ketosis. The paper presents comparative analysis of results of clinical and anamnestic examination of children depending on the severity of the course of pathology. Patients with less pronounced signs of acetonemic syndrome were characterized by higher occurrence of acetonemia per year, longer period of breastfeeding, more frequently compromised individual allergic anamnesis. Patients with severe acetonemic syndrome differed by higher infectious index, a tendency to bigger body mass indices, association with exacerbated gastroduodenal pathology.